High-throughput strategies for monoclonal antibody screening: advances and challenges - Xiao-Dong Wang; Bao-Ying Ma; Shi-Ying Lai; Xiang-Jing Cai; Yan-Guang Cong; Jun-Fa Xu; Peng-Fei Zhang (Journal of Biological Engineering)
Abstract Antibodies characterized by high affinity and specificity, developed through high-throughput screening and rapid preparation, are crucial to contemporary biomedical industry. Traditional antibody preparation via the hybridoma strategy faces challenges like low efficiency, long manufacturing cycles, batch variability and labor intensity. Advances in molecular biology and gene editing technologies offer revolutionary improvements in antibody production. New high-throughput technologies like antibody library display, single B cell antibody technologies, and single-cell sequencing have significantly cut costs and boosted the efficiency of antibody development. These innovations accelerate commercial applications of antibodies, meeting the biopharmaceutical industry's evolving demands. This review explores recent advancements in high-throughput development of antibody, highlighting their potential advantages over traditional methods and their promising future.